Techniques of Force and Pressure Measurement in the Small Joints of the Wrist. (January 2018) - Schreck, Michael J.; Kelly, Meghan; Canham, Colin D.; Elfar, John C.
Background: The alteration of forces across joints can result in instability and subsequent disability. Previous methods of force measurements such as pressure-sensitive films, load cells, and pressure-sensing transducers have been utilized to estimate biomechanical forces across joints and more recent studies have utilized a nondestructive method that allows for assessment of joint forces under ligamentous restraints.Methods: A comprehensive review of the literature was performed to explore the numerous biomechanical methods utilized to estimate intra-articular forces.Results: Methods of biomechanical force measurements in joints are reviewed.Conclusions: Methods such as pressure-sensitive films, load cells, and pressure-sensing transducers require significant intra-articular disruption and thus may result in inaccurate measurements, especially in small joints such as those within the wrist and hand. Non-destructive methods of joint force measurements either utilizing distraction-based joint reaction force methods or finite element analysis may offer a more accurate assessment; however, given their recent inception, further studies are needed to improve and validate their use.